Evaluation of lameness detection using radar sensing in ruminants. (9th November 2019) - Busin, Valentina; Viora, Lorenzo; King, George; Tomlinson, Martin; LeKernec, Julien; Jonsson, Nicholas; Fioranelli, Francesco
Abstract : Background: Lameness is a major health, welfare and production‐limiting condition for the livestock industries. The current 'gold‐standard' method of assessing lameness by visual locomotion scoring is subjective and time consuming, whereas recent technological advancements have enabled the development of alternative and more objective methods for its detection. Methods: This study evaluated a novel lameness detection method using micro‐Doppler radar signatures to categorise animals as lame or non‐lame. Animals were visually scored by veterinarian and radar data were collected for the same animals. Results: A machine learning algorithm was developed to interpret the radar signatures and provide automatic classification of the animals. Using veterinary scoring as a standard method, the classification by radar signature provided 85 per cent sensitivity and 81 per cent specificity for cattle and 96 per cent sensitivity and 94 per cent specificity for sheep. Conclusion: This radar sensing method shows promise for the development of a highly functional, rapid and reliable recognition tool of lame animals, which could be integrated into automatic, on‐farm systems for sheep and cattle.